Rebel or Revolutionary? Jack Kavanagh and the Early Years of the Communist Movement in Vancouver, 1920-1925 - Akers, David (Labour/Le Travailleur, 1992)
Abstract In the history of Canadian labour and the left from 1900 to 1925 the radical life of Jack Kavanagh represents an important link between the politics of pre-war socialism and post-war communism. A prominent trade union leader and revolutionary propagandist in Vancouver, he was a founding member of the Communist Party of Canada in 1921 and its first provincial chairman in British Columbia. At the level of leadership, however, the foundation period of the communist movement in Vancouver was dominated by recurring disputes between Kavanagh and the party centre in Toronto, suggesting a kind of regional factionalism. This article reviews that historical experience and assesses Kavanagh's place in Canada's radical heritage.